On-line preconcentration and cyclodextrin-modified micellar electrokinetic chromatography method for chiral separation of hexaconazole, penconazole and myclobutanil - Wan Ibrahim, Wan Aini (Faculty of Science, Universiti Teknologi Malaysia, 2009)
A method for the on-line preconcentration and chiral separation of three chiral triazole fungicides, namely hexaconazole, penconazole and myclobutanil is reported. Simultaneous enantioseparation of the three triazole fungicides was successfully achieved by using CD-MEKC system containing 40 mM hydroxypropyl-Î³-CD and 50 mM sodium dodecyl sulphate in 25 mM phosphate buffer (pH 3.0) solution. Stacking with a reverse migrating micelle (SRMM) and sweeping were used as two on-line preconcentration methods to enhance the concentration sensitivity. Results indicate that sweeping-CD-MEKC is better than SRMMCD-MEKC in terms of the sensitivity enhancement factor (SEF) of the three triazole fungicides. This is the first report on the simultaneous chiral separation of three triazole fungicides by on-line-CD-MEKC method.